Микроморфологическое строение пищеварительного тракта острицы — Enterobius vermicularis (Linnaeus, 1758) - Лосева, Н.Г. (Вестник зоологии, 1970)
Изучалось микроморфологическое строение различных отделов пищеварительной трубки острицы. Были использованы обычные гистологические методики с заливкой объекта в парафин. Установлено, что стома имеет довольно упрощенное строение, ткань пульпы губ напоминает соединительную ткань позвоночных; пищевод состоит из мускульной, эпителиальной нервной и железистой тканей, имеющих синцитмальный характер, гликоген в кишечнике распределен неравномерно — наибольшее его количество находится в среднем отделе последнего. As a result of studying the fine morphological structure of digestive tract in Enterobius vermicularis it was established that stoma has a rather simple structure — esophagus begins from the very base of lips. The pulp of lips, surrounded by cuticle, consists of tissue, resembling the connective tissue of the vertebrates. Esophagus of E. vermicula-ris, as well as that of the other nematodes studied by the author, has four types of tissues: muscular, epithelial, nerve and glandular, which are of syncytial type. Intestine in E. vermicularis consists of one-layer cylindrical epithelium. During histochemical investigation it was found that glycogen in the intestine is distributed nonuniformly, its maximum i% in the middle part.